Changes in the Synovial Fluid Cytokine Profile of the Knee Between an Acute Anterior Cruciate Ligament Injury and Surgical Reconstruction. Issue 2 (February 2022) - Kingery, Matthew T.; Anil, Utkarsh; Berlinberg, Elyse J.; Clair, Andrew J.; Kenny, Lena; Strauss, Eric J.
Background: Changes in the intra-articular inflammatory state during the immediate period after an acute anterior cruciate ligament (ACL) rupture are not well defined. Purpose: To evaluate changes in the concentration of select proinflammatory and anti-inflammatory synovial fluid cytokines during the interval between an ACL injury and surgical reconstruction. Study Design: Descriptive laboratory study. Methods: In patients with an acute ACL injury, a synovial fluid sample was obtained from the injured knee during the initial office visit within 2 weeks of the inciting traumatic event. An additional synovial fluid sample was collected at the time of ACL reconstruction just before the surgical incision. Synovial fluid samples from both the acute injury and the surgery time points were processed with a protease inhibitor, and the concentrations of 10 cytokines of interest were measured using a multiplex magnetic bead immunoassay. The primary outcome was the change in cytokine concentrations between time points. Results: A total of 20 patients with a mean age of 30.2 ± 8.3 years were included. The acute injury synovial fluid samples were collected at 6.6 ± 3.8 days after the injury. The surgical synovial fluid samples were collected at 31.6 ± 15.6 days after the acute injury samples. Based on a series of linear mixed-effects models to control for the effect of concomitant meniscal injuries and by-patient variability, there was a statistically significant increase in the concentrations of RANTES and bFGF and a statistically significant decrease in the concentrations of IL-6, MCP-1, MIP-1β, TIMP-1, IL-1Ra, and VEGF between time points. Conclusion: This study demonstrates the ongoing alterations in the intra-articular microenvironment during the initial inflammatory response in the acute postinjury period. We identified 6 synovial fluid cytokines that significantly decreased and 2 that significantly increased between the first clinical presentation shortly after the injury and the time of surgery 1 month later. Clinical Relevance: This study describes the molecular profile of the inflammatory changes between the time of an acute ACL injury and the time of surgical reconstruction 1 month later. A greater understanding of the acute inflammatory response within the knee may be helpful in identifying the optimal timing for a surgical intervention that balances the risk of chondral damage with the likelihood of successful, well-healed reconstruction.